2017
DOI: 10.1002/wics.1396
|View full text |Cite
|
Sign up to set email alerts
|

Unit root tests

Abstract: Unit roots are nonstationary autoregressive (AR) or autoregressive moving average (ARMA) time series processes which may include an intercept and/or a trend. These processes are used often in economics and finance, but can also be found in other scientific fields. Unit root tests address the null hypothesis of a unit root, and an alternative hypothesis of a stationary (or trend stationary) time series. Critical values for unit root tests are typically derived via simulation of limiting distributions expressed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 38 publications
0
13
0
1
Order By: Relevance
“…For this, the study adopted the Augmented Dickey Fuller This (ADF) unit root test (Dickey 1976;Dickey & Fuller 1979;Diebold & Kilian 2000;Aritova & Fedorova 2016;Herranz 2017). Subsequently the study employed the Akaike Information Criteria (AIC) in order to select the optimum lag-length for the estimation modelling (Akaike 1969;Akaike 1974;Ivanov & Kilian 2005;Gutierrez et al 2009).…”
Section: Methodsmentioning
confidence: 99%
“…For this, the study adopted the Augmented Dickey Fuller This (ADF) unit root test (Dickey 1976;Dickey & Fuller 1979;Diebold & Kilian 2000;Aritova & Fedorova 2016;Herranz 2017). Subsequently the study employed the Akaike Information Criteria (AIC) in order to select the optimum lag-length for the estimation modelling (Akaike 1969;Akaike 1974;Ivanov & Kilian 2005;Gutierrez et al 2009).…”
Section: Methodsmentioning
confidence: 99%
“…The unit roots test was conducted on three variables to test for stationarity or non-stationarity in the model amongst the variables. Herranz opined that unit roots are nonstationary autoregressive (AR) or autoregressive moving-average (ARMA) time series processes [5] that has 1 as a valid root of the characteristic polynomial [3]. The results showed that we can reject the null hypothesis that the series has a unit roots on grounds that the Trace-statistic is Greater than the Probability value for all variables in the series at levels.…”
Section: Empirical Analysismentioning
confidence: 99%
“…Elde edilen test istatistikleri MacKinnon (1996) kritik değerleriyle karşılaştırılmakta, boş hipotez reddedilemediğinde seride birim kök olduğuna karar verilmektedir. Seride birim kök olması, o serinin durağan olmadığını ifade etmektedir (Herranz, 2017).…”
Section: Yöntemunclassified